Strategi Komunikasi Komisi Pemilihan Umum (KPU) Kabupaten Bangkalan dalam Meningkatkan Partisipasi Masyarakat - Zaenab, Siti; Hadiati Salisah, Nikmah (Jurnal Ilmu Komunikasi, 2019)
This research discusses how the communication strategy of the General Election Commission (KPU) of Bangkalan Regency to increase public participation in regional head elections. This study uses a qualitative approach to investigate more deeply the observed focus. The theory used is strategic planning theory. The results of this study are (1) the communication strategy of the Bangkalan Regency’s KPU to increase voter participation using conventional methods, (2) the beginner voter education strategy is one of the KPU strategies by paying special attention to first-time voters. They are high school students/equivalent, by cooperating with novice voter